BDNF-Akt-Bcl2 antiapoptotic signaling pathway is compromised in the brain of autistic subjects - Sheikh, Ashfaq M.; Malik, Mazhar; Wen, Guang; Chauhan, Abha; Chauhan, Ved; Gong, Cheng-Xin; Liu, Fei; Brown, William T.; Li, Xiaohong (Journal of neuroscience research, 2010)
Although the pathogenesis of autism is not understood, emerging evidence points to apoptotic mechanisms being involved in this disorder. However, it is not known whether apoptosis signaling is deregulated in the brain of autistic subjects. This study investigates how the apoptosis‐related proteins are regulated in the autistic brain. Our studies show that Bcl2 is significantly decreased, whereas the expression of p53 is increased, in the brain of autistic subjects in comparison with age‐matched controls. We also found that the expression and phosphorylation/activation of Akt kinase that regulates Bcl2 are significantly decreased in the autistic brain. The down‐regulation of Akt may result from a decreased concentration of brain‐derived neurotrophic factor (BDNF), the growth factor that modulates Akt activities. These results suggest that down‐regulation of the BDNF‐Akt‐Bcl2 antiapoptotic signaling pathway in the autistic brain could be one of the underlying mechanisms responsible for the pathogenesis of autism. © 2010 Wiley‐Liss, Inc.